2003
DOI: 10.1016/s0041-1345(03)00644-4
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from calcineurin inhibitors to mycophenolate mofetil in liver transplant recipients with diabetes mellitus

Abstract: Diabetes mellitus, a frequent metabolic complication in liver transplant recipients, may be produced by the diabetogenic effect of calcineurin inhibitors cyclosporine and tacrolimus. The aim of this study was to investigate the safety and metabolic effects of a gradual switch from cyclosporine or tacrolimus to mycophenolate mofetil among 12 diabetic liver transplant recipients. One patient was withdrawn from the study due to gastrointestinal side effects. Of the 11 remaining patients, cyclosporine or tacrolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There is substantial evidence in the literature that both calcineurin inhibitors (particularly tacrolimus) and steroids significantly increase the risk of developing IR and posttransplant diabetes mellitus (16,17,36,37). In this study, only corticosteroids were found to be predictive of IR.…”
Section: Discussionmentioning
confidence: 60%
“…There is substantial evidence in the literature that both calcineurin inhibitors (particularly tacrolimus) and steroids significantly increase the risk of developing IR and posttransplant diabetes mellitus (16,17,36,37). In this study, only corticosteroids were found to be predictive of IR.…”
Section: Discussionmentioning
confidence: 60%
“…When CNI withdrawal was compared with CNI minimization with mycophenolate mofetil introduction, 62.5% vs. 50–60% had normalization of SCr, respectively (85). Use of mycophenolate mofetil to withdraw CNI was associated with improvement in SCr in 77–100% of patients and an increase in CrCl of about 9–11 mL/min (86–92). Expectedly, a study of diabetic patients with normal renal function demonstrated no improvement in SCr at six months (92).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Use of mycophenolate mofetil to withdraw CNI was associated with improvement in SCr in 77–100% of patients and an increase in CrCl of about 9–11 mL/min (86–92). Expectedly, a study of diabetic patients with normal renal function demonstrated no improvement in SCr at six months (92). Complete CNI withdrawal was achieved in 45–100% of patients, leading to better renal function than those maintained on low‐dose CNI (Fig.…”
Section: Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduction of tacrolimus dose in liver transplant patients in whom NODM develops may be of only limited benefit, and switching from tacrolimus to cyclosporine may be appropriate 51, 52. A further option may be switching patients with NODM to a calcineurin inhibitor–free regimen; preliminary evidence from a study of 12 liver transplant patients, of whom 5 were successfully converted to mycophenolate mofetil, suggests that this may be a feasible strategy to significantly improve glycemic control 53. However, selection of immunosuppression regimen in high‐risk patients to minimize risk of NODM developing should never jeopardize graft survival.…”
Section: Interventionmentioning
confidence: 99%